2020
DOI: 10.1097/or9.0000000000000039
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviours of Indigenous and non-Indigenous cancer survivors living in regional and remote geographic areas of Australia: a short report

Abstract: Background: Health behaviors are becoming increasingly recognized as important for cancer survivors in optimizing health after diagnosis. The current study aims to describe adherence to health behaviour guidelines in a sample of Indigenous and non-Indigenous cancer patients in Australia's Northern Territory. Methods: A structured survey collecting self-reported sociodemographic and health behaviour data was administered to a sample of cancer patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 9 publications
0
7
2
Order By: Relevance
“…In the present study, relevant individual food types within the following six food groups were assessed due to their importance to cancer [ 19 ] and/or their inclusion in previous studies conducted among cancer survivors [ 3 5 , 11 , 12 ]: fruits, vegetables, cereals/breads/grains, whole red meats, processed red meats, and alcohol. For each individual food type (e.g., salad, vegetables (except potatoes) and beans/pulses for vegetables) in the I.CAN FFQ, adherence to dietary guidelines was determined using recommendations published in the Australian Dietary Guidelines [ 20 ] or the Australian Guidelines to Reduce Health Risks from Drinking Alcohol [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, relevant individual food types within the following six food groups were assessed due to their importance to cancer [ 19 ] and/or their inclusion in previous studies conducted among cancer survivors [ 3 5 , 11 , 12 ]: fruits, vegetables, cereals/breads/grains, whole red meats, processed red meats, and alcohol. For each individual food type (e.g., salad, vegetables (except potatoes) and beans/pulses for vegetables) in the I.CAN FFQ, adherence to dietary guidelines was determined using recommendations published in the Australian Dietary Guidelines [ 20 ] or the Australian Guidelines to Reduce Health Risks from Drinking Alcohol [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Few studies, however, have reported on adherence to dietary guidelines and/or associated factors among rural cancer survivors. In Australia, for example, two studies are known to have examined rural cancer survivors’ adherence to dietary guidelines [ 11 , 12 ]. In an Australian cross-sectional study conducted among 63 cancer survivors in the Northern Territory (NT), the percentages of participants meeting dietary guidelines were 76% for whole red meat, 75% for alcohol, 73% for fruits, 33% for processed meats, and 10% for vegetables [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interview also captured self-reported socio-demographic data, including age, gender, Indigenous status, marital status, employment status, educational attainment, main language spoken at home, and residence by postcode and community name [ 17 ]. Medical chart reviews were conducted using a standard data collection form by a member of the cancer care team to gather participant’s clinical information (diagnosis date, cancer staging at diagnosis, cancer type, and treatment regimen (current or planned treatments).…”
Section: Methodsmentioning
confidence: 99%
“…A report from Tollosa et al [9] using data from the Australian Longitudinal Study on Women's Health showed that 41%, 36%, and 85.1% of female cancer survivors were not engaging in the health recommendations for physical activity, fruit intake, and vegetable intake, respectively. More recently, Elder-Robinson et al [10] investigated health behaviours of Australian cancer survivors in rural and remote areas, demonstrating that up to 27% had reduced their fruit and vegetable intake and 70% had reduced their physical activity since their cancer diagnosis.…”
mentioning
confidence: 99%